Exam ref 70-741 : Networking with Windows Server 2016 / Andrew Warren - Warren, Andrew
Microsoft Exam 70-741 is for IT Pros interested in enhancing their skills for the latest version of Windows Server. This exam validates skills and knowledge for configuring advanced tasks required to deploy, manage, and maintain a Windows Server 2016 infrastructure, such as fault tolerance, certificate services, and identity federation. Passing this exam along with two other exams is required for MCSA and MCSE certifications. The Exam Ref is the official study guide for Microsoft certification exam 70-741. Featuring concise, objective-by-objective reviews and strategic case scenarios and Thought Experiments, exam candidates get professional-level preparation for the exam. The Exam Ref helps candidates maximize their performance on the exam and sharpen their job-role skills. It organizes material by the exam's objective domains Focus is on the skills measured on the exam: Implement Domain Name System (DNS) Implement DHCP Implement IP Address Management (IPAM) Implement network connectivity and remote access solutions Implement core and distributed network solutions Implement an advanced network infrastructure This Microsoft Exam Ref: Organizes its coverage by the “Skills measured” posted on the exam webpage Features strategic, what-if scenarios to challenge you Points to in-depth material by topic for exam candidates needing additional review Assumes you are an IT pro looking to validate your skills in and knowledge of installing and configuring Windows Server 2016.